A quinoline alkaloid rich Quisqualis indica floral extract enhances the bioactivity. Issue 10 (19th May 2021) - Rout, Prasant Kumar; Kumar, Prashant; Rao, Y. Ramachandra; Kumar, Anant; Bawankule, Dnyaneshwar U.; Singh, Ruchi; Singh, Kijay Bahadur; Chanotiya, Chandan Singh; Naik, S. N.
Abstract: A volatile alkaloid quinoline-4-carbonitrile (QCN) was isolated from the floral extract of Quisqualis indica . Major compounds were trans -linalool oxide (1.0, 4.5%), methyl benzoate (1.0, 4.0%), 2, 2, 6-trimethyl-6-vinyl-tetrahydropyran-3-one (7.4, 17.8%), 2, 2, 6-trimethyl-6-vinyl-tetrahydropyran-3-ol (1.0, 1.2%), ( E, E )-α-farnesene (29.1, 16.1%), QCN (5.7, 1.3%) in live and picked flowers, respectively. Flower compositions were altered due to change in enzymatic reaction at the time of picking. Some rearrangements of oxygenated terpenoids occurred in the process of hydrodistillation to obtain essential oil. Chemical synthesis of QCN and its selectively reduced products derived from QCN were prepared through green reaction process. The catalytic modification of QCN has produced quinoline-4-methylamine; the later compound has shown enhanced bio-activities. QCN and floral extract (absolute) have shown potential anti-inflammatory and antioxidant activities. Besides, floral absolute has shown significant anti-inflammatory and antioxidant activities due to improved QCN (19.7%) content to synergize amongst terpenoids and benzenoids as compared to the essential oil with 1.1% of QCN. GRAPHICAL ABSTRACT: